1996
DOI: 10.1161/01.cir.94.6.1239
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neutrophil-Platelet Adhesion in Patients With Unstable Angina

Abstract: Thus, this study demonstrates that increased neutrophil-platelet adhesion may contribute to neutrophil activation in unstable angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
257
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(270 citation statements)
references
References 39 publications
6
257
1
6
Order By: Relevance
“…The importance of neutrophil-platelet adhesive interactions has been noted in the circulation of patients with unstable angina 50 and after coronary angioplasty. 51 Recently, it has been shown that blockade of the selectins with an analogue of sLe x reduced intimal hyperplasia after balloon injury in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of neutrophil-platelet adhesive interactions has been noted in the circulation of patients with unstable angina 50 and after coronary angioplasty. 51 Recently, it has been shown that blockade of the selectins with an analogue of sLe x reduced intimal hyperplasia after balloon injury in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies with un-separated leukocyte populations reveal a significant increase in platelet-leukocyte complexes in allergic mice and in human asthmatics (Pitchford et al, 2003(Pitchford et al, , 2005. Similar processes occur in patients with COPD (Ferroni et al, 2000), atherosclerosis (Arber et al, 1991;Ott et al, 1996;Neumann et al, 1997;Sarma et al, 2002;Huo et al, 2003) and RA (Joseph et al, 2001;Bunescu et al, 2004). In this regard, experimental models of disease have provided evidence for a requirement of platelets in pulmonary eosinophil and lymphocyte recruitment in rabbits, guineapigs and mice in models of allergic inflammation (LellouchTubiana et al, 1988;Coyle et al, 1990;Pitchford et al, 2003Pitchford et al, , 2005; and neutrophil and monocyte recruitment in atherosclerosis (Arber et al, 1991;Neumann et al, 1997;Hayward et al, 1999) and RA (Schmitt-Sody et al, 2005).…”
Section: Leukocyte Recruitment and Activation: Influence Of Plateletsmentioning
confidence: 97%
“…These studies suggest a participation of platelets in the inflammatory responses as well as the recognized events leading to thrombus formation. Platelet binding to leukocytes occurs during acute coronary events, and these heterotypic aggregates are formed as a result of activation by inflammatory mediators (Arber et al, 1991;Ott et al, 1996) and are largely bound via P-selectin/P-selectin glycoprotein ligand-1 (PSGL-1) interactions (Sarma et al, 2002). It is worth noting that an increased expression of CD40L occurs on the surface of platelets in acute coronary syndromes (Garlichs et al, 2001), although the significance of this is not yet known, it reveals another mechanism whereby platelets may further stimulate the inflammatory response during atherosclerosis.…”
Section: Platelet Activation In Atherosclerosismentioning
confidence: 99%
“…The presence of increased leukocyte-platelet binding has been shown in patients with acute coronary syndromes (25). Adhesion of platelets to circulating myeloid leukocytes in vitro and in vivo is related to platelet activation (26).…”
Section: Myocardial Infarction; Mpv Mean Platelet Volume; Wbc Whitmentioning
confidence: 99%